Ecolinguistic-Based Development of General Linguistics Materials Using Phonological and Lexical Variations of Angkola Batak (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study develops ecolinguistics-oriented General Linguistics teaching materials grounded in Angkola Batak phonological and lexical variation to support contextualized learning and local language preservation in Indonesian universities. Method: Using an R&D approach with the ADDIE model (analysis, design, development, implementation, evaluation), the product was validated and tested with five expert validators, two General Linguistics lecturers, and 60 Indonesian Language and Literature Education students at Universitas Muhammadiyah Tapanuli Selatan. Instruments included expert validation sheets, lecturer and student practicality questionnaires, and pre–post achievement tests. Data were analyzed descriptively and inferentially using the Content Validity Index (CVI), Cronbach’s Alpha, N-Gain, and a paired-sample t-test. Results: The teaching material showed very high validity (CVI = 0.91), strong reliability (α = 0.86), and high practicality (overall practicality = 91%). Effectiveness results indicated a significant improvement in learning outcomes, with mean scores increasing from 70.27 (pre-test) to 88.56 (post-test) and an N-Gain of 0.60 (moderate–high; p < 0.05). The material enhanced students’ analytical skills in phonology and lexicon while fostering ecolinguistic awareness of regional linguistic diversity. Novelty: The study offers a replicable framework for operationalizing applied ecolinguistics in linguistic pedagogy through local language data.